Sosialisasi Perhitungan Numerik Terkait Forecasting Pengunjung Hotel (Studi di Hotel Primebiz Surabaya) - Firman Yudianto; Teguh Herlambang; Mohamad Yusak Anshori; Mukhtar Adinugroho; Afib Rulyansah (Indonesia Berdaya, 2023)
The huge increase in the number of hotels has led to stiff competition. In the past, competition generally emphasized the quality of hotel services and facilities, but now it is also necessary to improve the ability to manage hotels efficiently. The Covid pandemic has forced hotel management to think and work hard to increase revenue and reduce costs without reducing the quality of service to guests who stay overnight. Hotels that are managed efficiently will be able to win the competition. Therefore, making forecast models and accurate estimates will help hotel managers manage hotels effectively and efficiently, so it is necessary to develop software for forecasting and estimation systems. In this community service activity, we synergize management knowledge with mathematics so that it can be used more easily, accurately, effectively and efficiently in hotel management. In this activity socialization of simulations or numerical calculations related to hotel visitor forecasting is carried out.